2010
DOI: 10.1016/j.ipm.2009.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual language models for domain-specific retrieval

Abstract: a b s t r a c tOver the years, various meta-languages have been used to manually enrich documents with conceptual knowledge of some kind. Examples include keyword assignment to citations or, more recently, tags to websites. In this paper we propose generative concept models as an extension to query modeling within the language modeling framework, which leverages these conceptual annotations to improve retrieval. By means of relevance feedback the original query is translated into a conceptual representation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…From the practical standpoint, the MLE method does not adequately distinguish the importance of term occurrences. This has also been noted in Meij et al (2010) where EM estimation is used. We have noted that the EM method achieves a similar effect as the TF-IDF method does but is more computationally expensive.…”
Section: 3me Modelmentioning
confidence: 58%
See 3 more Smart Citations
“…From the practical standpoint, the MLE method does not adequately distinguish the importance of term occurrences. This has also been noted in Meij et al (2010) where EM estimation is used. We have noted that the EM method achieves a similar effect as the TF-IDF method does but is more computationally expensive.…”
Section: 3me Modelmentioning
confidence: 58%
“…Differing from treating concepts as a pivot language as in Meij et al (2010), our models enhance the relevance model by mining the associations between concepts and other elements, namely, terms, documents, and user's queries.…”
Section: 3information Retrieval Using Meshmentioning
confidence: 99%
See 2 more Smart Citations
“…Ozcan et al [4] adopted ontologies to represent concepts which are expanded by using WordNet. Meij et al [16] showed that discriminative semantic annotations of documents using domain-specific ontologies, such as MeSH, can effectively improve retrieval effectiveness.…”
Section: Related Workmentioning
confidence: 99%